2009
DOI: 10.1007/s10620-009-0854-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Enteric-Coated, Delayed-Release Peppermint Oil on Irritable Bowel Syndrome

Abstract: Herbal remedies, particularly peppermint, have been reported to be helpful in controlling symptoms of irritable bowel syndrome (IBS). We conducted a randomized double-blind placebo-controlled study on 90 outpatients with IBS. Subjects took one capsule of enteric-coated, delayed-release peppermint oil (Colpermin) or placebo three times daily for 8 weeks. We visited patients after the first, fourth, and eighth weeks and evaluated their symptoms and quality of life. The number of subjects free from abdominal pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 19 publications
2
101
0
7
Order By: Relevance
“…Based on these studies, at best peppermint has a marginal efficacy. However, it is important to note that there are no adverse reactions although there was a high dropout rate in one trial [72] .…”
Section: Peppermintmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on these studies, at best peppermint has a marginal efficacy. However, it is important to note that there are no adverse reactions although there was a high dropout rate in one trial [72] .…”
Section: Peppermintmentioning
confidence: 96%
“…Table 1 lists 7 studies that examined the benefits of peppermint in IBS [67][68][69][70][71][72] . Based on these studies, at best peppermint has a marginal efficacy.…”
Section: Peppermintmentioning
confidence: 99%
“…The most recent review included 5 trials for a total of 482 patients (107)(108)(109)(110)(111); it showed a statistically significant positive effect of peppermint oil versus placebo, with a NNT of 3 (95% CI: 2-4) (90). However, there was significant heterogeneity among studies.…”
Section: Efficacymentioning
confidence: 99%
“…Good tonic for the stomach and liver. Eliminates thread worms in children, relieves colic due to worms, and due to indigestion It is considered to be good for digestion and effective in the treatment of irritable bowl syndrome (Cappello et al 2007;Merat et al 2010) Therapeutic uses of edible plants in Bangalore city, India 309…”
Section: Mentha Sativamentioning
confidence: 99%